CGM-MLP_natcomm2023_Cu-C-O_deposition - Di Zhang; Peiyun Yi; Xinmin Lai; Linfa Peng; Hao Li (ColabFit, 2024)
Training simulations from CGM-MLP_natcomm2023 of carbon deposition on a Cu surface. This appears similar to CGM-MLP_natcomm2023_CU-C_deposition, as there are no O atoms present in this set. This dataset was one of the datasets used in training during the process of producing an active learning dataset for the purposes of exploring substrate-catalyzed deposition on metal surfaces such as Cu(111), Cr(110), Ti(001), and oxygen-contaminated Cu(111) as a means of controllable synthesis of carbon nanomaterials. The combined dataset includes structures from the Carbon_GAP_20 dataset and additional configurations of carbon clusters on a Cu, Cr and Ti surfaces.
Keywords: ColabFit; Dataset; AgPd_NPJ_2021; Materials Science; https://id.loc.gov/authorities/subjects/sh85082094.html; Machine Learning; https://id.loc.gov/authorities/subjects/sh85079324.html; Techniques/Computational Techniques/First-principles calculations; Techniques/Computational Techniques/Machine Learning; Techniques/Computational Techniques/Molecular Dynamics; Research Areas/Atomic & molecular structure/Potential energy surfaces; Research Areas/Electronic structure/Interatomic & molecular potentials